Development and in vitro characterization of a multiparticulate delivery system for acyclovir-resinate complex. (3rd July 2016) - Jain, Sunil K.; Kumar, Ajay; Kumar, Amrish; Pandey, Aditya N.; Rajpoot, Kuldeep
Abstract : Context: Herpes viruses cause threatening infections in humans and stand second as causative agents for most human viral diseases, after influenza and cold viruses. Objective: A novel multiparticulate delivery system for acyclovir (ACV), based on ion-exchange resin, was developed to achieve a gastro-mucoadhesive effect in order to effectively combat the herpes simplex virus. Materials and methods: A combination of ACV and cholestyramine resin was optimized and further entrapped within sodium alginate and Carbopol microbeads. The developed systems were evaluated for drug entrapment efficiency (DEE), percentage of mucoadhesion, and in vitro release characteristics in simulated gastric ﬂuid (SGF, pH 1.2). Results: With the aid of scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy (FTIR), the interaction of the resinate and polycations with alginate has been revealed, which consequently supports the formation of the membrane by the polyelectrolyte complex. The in vitro drug release studies demonstrate that formulations without the drug-resin complex (DRC) released the drug more rapidly than formulations containing DRC, which released the drug in a controlled manner, due the formation of a complex between drug and resin. Discussion and conclusion: Preliminary results from this study suggest that these DRC-entrapped microbeads may be used to incorporate other antiviral drugs and could be effective against infections caused by herpes viruses. Such formulations developed could be subjected to in vivo studies in future, in order to prove complete clearance of herpes infections.